Законодавче забезпечення розвитку інноваційно-інтегрованих структур як складова національної безпеки держави в умовах соціально-економічної нестабільності - Бугаєва, М. В.; Орлова, А. А.; Buhaieva, M.; Orlova, A. (My University, 2017)
Сьогодні процеси швидкої глобалізації та зростання динамізму світового економічного простору стали визначальними для побудови нової моделі економічного розвитку національної економічної системи - інноваційної моделі. Інноваційна модель економічного розвитку стає основою, яка визначає економічну міць країни та її перспективи на світовому ринку. У сучасному світі країни змушені шукати прийнятну модель економічного розвитку, яка забезпечувала б національну конкурентоспроможність і орієнтувала б національну економіку на довгострокове зростання. Одним з напрямків такого зростання стає розширення інтеграційних процесів і поява інноваційно-інтегрованих структур, які забезпечать становлення країни як високотехнологічної конкурентної держави. Існування проблем, пов'язаних із законодавчою підтримкою розвитку інноваційно-інтегрованих структур як невід'ємної частини національної безпеки держави в умовах соціально-економічної нестабільності, визначає актуальність наших досліджень. Тому сьогодні актуальним є аналіз існуючого національного законодавства, що регулює інноваційну та інвестиційну галузі, питання законодавчої підтримки розвитку інноваційно-інтегрованих структур і пошук напрямів його вдосконалення. Національне законодавство, що регулює розвиток інноваційно-інтегрованих структур України, є фрагментарним і суперечливим, і тому воно недосконале. Автори визначили, що впровадження прийнятих законів в інноваційній та інвестиційній сферах незадовільно; реалізація ряду законів в Україні стримується. Автори виявили, що ряд важливих законопроектів про регулювання інвестиційної та інноваційної сфери не розглядаються, що не допрацьовуються та / або не виводяться без розгляду альтернативних протягом тривалого часу. Виявлено нестійкість венчурної діяльності. Це перешкоджає розвитку таких форм для підтримки інновацій, як венчурні фонди. Для України характерний низький рівень державного фінансування науки, науки і техніки. В Україні немає реальної стратегії управління інноваціями. Авторами досліджено підходи і кількісні рекомендації по впровадженню структурних змін в Стратегії розвитку України на період до 2020 року. Основна мета - збільшити вплив інновацій на економічне зростання України в цій Стратегії. Автори проаналізували і узагальнили існуюче національне законодавство України, яке регулює інноваційну та інвестиційну сфери. Виділили законодавче забезпечення розвитку інноваційно-інтегрованих структур поряд з переглядом національного законодавства. Важливим напрямом у розвитку інноваційно-інтегрованих структур України є створення законодавчої бази, що забезпечує концептуальну державну політику, інвестиції, фінансове забезпечення інновацій, ефективний розвиток і функціонування наукової сфери і в той же час процесу комерціалізації його інтелектуальних результатів, реального партнерства між державним і приватним секторами. Необхідно врахувати витрати в Державному бюджеті України на можливість фінансової підтримки розвитку інноваційно-інтегрованих структур. Завдання податкових стимулів для суб'єктів бізнесу, зайнятих в інноваційній галузі, повинна бути вирішена. Також необхідно відновити реалізацію цільової економічної програми зі створення інноваційної інфраструктури в Україні, яка припинила свою діяльність в 2013 році. На національному, регіональному та місцевому рівнях можуть бути розроблені напрями вдосконалення законодавчої підтримки розвитку інноваційно-інтегрованих структур для формування національної інноваційної системи України в умовах соціально-економічної нестабільності. Today the processes of rapid globalization and the growth of the dynamism of the global economic space become determinative for building a new model for the economic development of the national economic system - the innovation model. The innovation model of economic development is becoming the foundation that determines the economic strength of the country and its prospects on the global market. In the modern world countries are forced to search for the acceptable model of economic development that would ensure national competitiveness and orient the national economy for long-term growth. The expansion of integration processes and the emergence of innovation-integrated structures that will ensure the country's emergence as a high-tech competitive state become one of the directions of such growth. The existence of problems that related to the legislative support of the development of innovation-integrated structures as an integral part of the national security of the state in the conditions of socio-economic instability determines the topicality of our research. Therefore, the analysis of the existing national legislation that regulates the innovation and investment industry, the issues of legislative support of the development of innovation-integrated structures, and the search for directions for its improvement are relevant today. National legislation that regulates the development of Ukraine's innovation-integrated structures is fragmentary and contradictory, and therefore it is imperfect. The authors determined that the implementation of the adopted laws in the innovation and investment sphere is unsatisfactory; the implementation of a number of laws in Ukraine is restrained. We found that a number of important draft laws on the regulation of investment and innovation sphere are not considered, are not being finalized and/or withdrawn without consideration of alternative ones for a long time. The unsettledness of venture activity was revealed. It prevents the development of such institutions to support innovation, such as venture funds. The low level of state funding for science, science and technology is characteristic of Ukraine. There is no real strategy to manage innovation in Ukraine. We have justified the approaches and quantitative guidelines for implementing structural changes in the Development Strategy of Ukraine for the period up to 2020. The main goal is to increase the influence of innovation on Ukraine's economic growth in this Strategy. We have analyzed and summarized the existing national legislation of Ukraine that regulates the innovation and investment sphere. We have isolated legislative support of the development of innovation-integrated structures along with the review of national legislation. The important direction in the development of the development of Ukraine's innovation-integrated structures is the creation of a legislative framework that will ensure conceptual public policy, investment, financial provision of innovation, effective development and functioning of the scientific sphere and in the same time the process of commercialization of its intellectual results, real partnership between the state and private sector. It is necessary to budget the certain costs in the State Budget of Ukraine for the possibility of financial support for the development of innovation-integrated structures. The task of tax incentives for business entities engaged in the innovation industry needs to be resolved. It is also necessary to resume the implementation of the targeted economic program for the creation of innovation infrastructure in Ukraine that has stopped its activities in 2013. The directions for improvement of legislative support of the development of innovation-integrated structures can be used at the national, regional and local levels to form the national innovation system of Ukraine in the conditions of socio-economic instability.
The legislative support of the development of innovative and integrated structures as the part of national security of the state in the conditions of social and economic instability
Keywords: законодавство; інноваційна сфера; інноваційна та інвестиційна діяльність; інноваційно-інтегровані структури; legislation; innovation sphere; innovation and investment activity; innovation-integrated structures